2004
DOI: 10.1111/j.1365-2885.2004.00574.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and pharmacokinetics of florfenicol in healthy sheep*

Abstract: A study on bioavailability and pharmacokinetics of florfenicol was conducted in 20 crossbred healthy sheep following a single intravenous (i.v.) and intramuscular (i.m.) doses of 20 and 30 mg/kg body weight (b.w.). Florfenicol concentrations in serum were determined by a validated high-performance liquid chromatography method with UV detection at a wavelength of 223 nm in which serum samples were spiked with chloramphenicol as internal standard. Serum concentration-time data after i.v. administration were best… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
20
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 25 publications
10
20
0
1
Order By: Relevance
“…These results are in agreement with the findings of previous studies on florfenicol performed in sheep (Ali et al 2003;Lane et al 2004), goats (Atef et al 2001;Ali et al 2003), calves (Varma et al 1986;Adams et al 1987;Decraene et al 1997) and broiler chickens (Shen et al 2003). However, Lobell et al (1994), Soback et al (1995) and Jianzhong et al (2004) found that the disappearance of florfenicol from the plasma after i.v. administration was described adequately by a three compartment term.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…These results are in agreement with the findings of previous studies on florfenicol performed in sheep (Ali et al 2003;Lane et al 2004), goats (Atef et al 2001;Ali et al 2003), calves (Varma et al 1986;Adams et al 1987;Decraene et al 1997) and broiler chickens (Shen et al 2003). However, Lobell et al (1994), Soback et al (1995) and Jianzhong et al (2004) found that the disappearance of florfenicol from the plasma after i.v. administration was described adequately by a three compartment term.…”
Section: Discussionsupporting
confidence: 91%
“…The value of AUC (59.44 l/kg/h) after i.v. administration of florfenicol in our study was similar to that recorded in sheep (Jianzhong et al 2004), camels (Ali et al 2003), and higher than goats (Atef et al 2001), chickens (Shen et al 2003), rabbits (Park et al 2007) and dogs (Kim et al 2011), which showed that florfenicol was distributed rapidly in dogs.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations